Community perception of odour pollution from landfills - Zaini Sakawi,; Sharifah Mastura SA,; Othman Jaafar,; Mastura Mahmud, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2011)
Odour pollution from landfill is one component of pollutants that affects human environment. Issues and odour complaints from the landfill had been made through the media, official channels and local public protests. This paper analyses feedback from the people living within 2 km radius of a landfill to gauge their perception and experience of being affected by odour pollution. One part of the study involved a perception survey to determine the influence of landfill odour on social, health, and comfort levels. The other part determined the level, duration and intensity of the unpleasant odours. The results showed that the strong offensive smell was normally experienced following rainfall events. Meteorological factors such as wind speed and wind direction were also considered to assess the acceptability of the local community of the smell nuisance. The findings also showed that the smell from the landfill had caused daily discomfort. In conclusion, the findings point to the imperative of mitigating measures being taken by the authorities concerned